Deal with it : negotiating the constraints of HDB home spaces. - Woo, Dianne Shu Mei. (2010)
The vast majority of Singaporeans live in Housing Development Board flats (Singapore high-rise public housing) beneath multiple layers of constraints surrounding their home space—their primary territories and often case, the most costly and important purchased good in their lives. Constraints experienced include such as uniform spaces, inability to influence rigid external features, strict policies, short tenures and high costs. The Singaporean must balance regulation, institution and the fulfilment of his private life.